Inhibition of PI3K/Akt/mTOR Signaling Pathway by Vitis Vinifera Phytocompounds: A Promising Strategy for Supressing Colorectal Cancer Growth and Metastasis - Alan S Mathew (International Journal of Cell Biology and Cellular Functions, 2023)
Objectives: Colorectal cancer was not typically identified a few decades ago. Today, with almost 900 000 fatalities each year, it is the fourth most dangerous cancer in the world. Colorectal cancer is responsible for about 10% of all cancer diagnoses annually and cancer-related deaths worldwide. It is the second most common type of cancer in women and the third most common type in men. Incidence and death are roughly 25% lower in women than in men. The PI3K/AKT/mTOR signaling system, which controls a wide range of cellular functions including survival, growth, angiogenesis metabolism, proliferation, and metastasis, is hyperactivated or changed in many cancer forms. Hence these proteins may be considered as therapeutic targets to supress colorectal cancer. In this study, the targeted proteins implicated in the etiology of various malignancies were examined for their pharmacological properties and therapeutic impact using the phytochemical components of Vitis vinifera. Methods: In this study, 203 phytochemicals from Vitis vinifera were selected to evaluate their compatibility with the PI3K, AKT, and mTOR target proteins. A virtual tool called PyRx was used to carry out the molecular docking. Data and molecular structures of the phytocompounds and proteins obtained from Indian medicinal plants, phytochemistry, and therapies, as well as PubChem, were used in the computer analysis. Several technologies, such as BIOVIA discovery studio software and PDBsum generator, were used to validate the protein structure. Using ADMET filters, the ligands' pharmacological evaluation was performed. Result: According to the results of molecular docking, the ligands Lupeol , 4-[(2R,3R)-3-(3,5-dihydroxyphenyl)-6-hydroxy-4-[(Z)-2-(4-hydroxyphenyl)vinyl]-2,3-dihydrobenzofuran-2-yl]benzene-1,2-diol, Procyanidin Dimer B7, Procyanidin B1, and Vitamin E had the highest binding affinity towards the three targeted proteins. Conclusion: These substances could make a good candidate for the management and suppression of cancer because they are effective against the proteins implicated in cancer development. To support these findings, in vitro study is still needed.
Keywords: Cancer; Docking; colorectal cancer; mammalian target of rapamycin; phosphatidylinositol 3-kinase; phytocompounds; vitis vinifera